N-Alkoxy-N-(dimethoxyphos-phoryl)ure-as AND Z-N- Alkoxy -1-(dimethoxyphosphoryloxy)-benzimidates - Shtamburg, V. G.; Штамбург, В. Г.; Kravchenko, Svitlana; Кравченко, Світлана Володимирівна; Klots, E. A.; Клоц, Є. О.; Shtamburg, V. V.; Штамбург, В. В.; Anishchenko, A. A.; Aніщенко, A. О.; Shishkina, S. V.; Шишкіна, С. В.; et al. (Східноукраїнського національного університету імені Володимира Даля, 2024)
The possibility of the nucleophilic substitution of the chlorine atom in N-alkoxy-N-chloroureas and in N-alkoxy-N-chlorobenzamides allow to create the new reaction strategies that give access to such new biological relevant scaffolds We have studied the interaction of trimethyl phosphite with N-alkoxy-N-chloroureas. The N-alkoxy-N-chloroureas 1a-d react with trimethyl phosphite in ether selectively forming the N-alkoxy-N-(dimethoxyphosphoryl)ureas 2–5. Можливість нуклеофільного заміщення атома хлору в N-алкокси-N-хлорсечовинах та N-алкокси-N-хлорбензамідах дозволяє створювати нові реакційні стратегії, що надають доступ до таких нових біологічно релевантних каркасів. Ми вивчали взаємодію триметилфосфіту з N-алкокси-N-хлорсечовинами. N-алкокси-N-хлорсечовини 1a-d реагують з триметилфосфітом в ефірі, селективно утворюючи N-алкокси-N-(диметоксифосфорил)сечовини 2–5.
N-Алкокси-N-(диметоксифосфорил)сечовини і Z-N- алкокси -1-(диметокси-фосфорилокси)бензіміди